2020
DOI: 10.1093/nsr/nwaa038
|View full text |Cite
|
Sign up to set email alerts
|

Aortic heterogeneity across segments and under high fat/salt/glucose conditions at the single-cell level

Abstract: The aorta, with ascending, arch, thoracic and abdominal segments, responds to the heartbeat, senses metabolites and distributes blood to all parts of the body. However, the heterogeneity across aortic segments and how metabolic pathologies change it are not known. Here, a total of 216 612 individual cells from the ascending aorta, aortic arch, and thoracic and abdominal segments of mouse aortas under normal conditions or with high blood glucose levels, high dietary salt, or high fat intake were profiled using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
44
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(51 citation statements)
references
References 78 publications
5
44
0
Order By: Relevance
“…Our study showed that there are 5 subtypes of vascular SMCs in the ascending aorta: synthetic (SMC_1), contractile (SMC_2), fibroblast-like (SMC_3), and inflammatory (SMC_4 and SMC_5) SMCs. The presence of synthetic, contractile, and fibroblast-like subpopulations is consistent with previous reports 15 , 16 , 37 . SMC_1 accounted for the highest proportion and expressed genes involved in cell proliferation and migration, but it expressed low levels of contractile genes.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our study showed that there are 5 subtypes of vascular SMCs in the ascending aorta: synthetic (SMC_1), contractile (SMC_2), fibroblast-like (SMC_3), and inflammatory (SMC_4 and SMC_5) SMCs. The presence of synthetic, contractile, and fibroblast-like subpopulations is consistent with previous reports 15 , 16 , 37 . SMC_1 accounted for the highest proportion and expressed genes involved in cell proliferation and migration, but it expressed low levels of contractile genes.…”
Section: Discussionsupporting
confidence: 92%
“…Qualified aortic cell suspensions were loaded onto a Single-Cell Instrument (10x Genomics GemCode Technology, CA) to generate single-cell Gel beads in EMulsion (GEMs, Single Cell 3′ Library and Gel Bead Kit V2 [10x Genomics]). The sequencing protocols have been described in a previous report 15 . Briefly, the single-cell suspension, reagents, gel beads, and partitioning oil were loaded onto 10x Chromium Chip B. Single-cell RNA was barcoded through reverse transcription in individual GEMs.…”
Section: Methodsmentioning
confidence: 99%
“…These subpopulations have gene expression patterns that are suggestive of functional specialization (e.g. angiogenesis, inflammatory responses, vasomotor control, extracellular matrix production) and are modulated by diet and blood pressure [83][84][85]. We have not addressed the mechanisms responsible for promoting altered endothelial cell clustering in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…The arrival of single-cell transcriptomics is now providing unprecedented opportunities to discover new immune cell subpopulations. Eleven immune cell subpopulations are identified in the aorta of atherosclerotic mice (13); however, only five or less subtypes are identified in healthy mice (14,15), suggesting a high degree of immune cell heterogeneity in the diseased vasculature. Different species, tissue, disease,…”
Section: Subtypes Of Immune Cells In Vasculaturementioning
confidence: 99%
“…The former expresses typical contractile proteins αSMA, MYH11, SM22α, and CNN1. When stimulated by injury or inflammation, VSMCs downregulate the expression of contractile genes, increase extracellular matrix (ECM) synthesis, and enhance secretion, migration, and proliferation (69), a motility-associated VTN high VSMCs has been identified as an intermediate switching type (15). Loss of VSMC characteristic is a key factor in vascular diseases such as atherosclerosis, aortic aneurysm, pulmonary hypertension, and restenosis (70).…”
Section: Subtypes Of Smooth Muscle Cells In Vasculaturementioning
confidence: 99%